Building a Code Stroke at Hospital without CT-scan Facilities - Wisni, Anggrieni; Nurhidayati, Eni; Anton, Secendry R.; Alifah, Nur; Murdiyanto, Joko (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: To determine the medical and management steps for building a code stroke at Rizki Amalia Medika Hospital. Methodology: his research is a descriptive qualitative study using a case report approach using observation and interview methods. Observations were carried out at in January-June 2024. The sample was obtained by purposive sampling method. Results: Landscape analysis is carried out on internal and external factors. The creation of a multidisciplinary team involves medical and nonmedical service units. The stroke protocol is carried out starting from pre-hospital, emergency unit, stroke code activation and administration of alteplase therapy for ischemic stroke. Training and education are carried out internally and externally to the hospital. Community socialization and education involve public campaigns and collaboration between elements. Improving the quality and analysis of data focuses on collecting medical data, medical audits, and feedback loops. In January to June 2024, there were 7 ischemic stroke visits with 57% receiving alteplase therapy. The success of alteplase therapy in ischemic stroke patients at Rizki Amalia Medika Hospital was 100%. Conclusion: Building a code stroke requires a comprehensive approach. By prioritizing rapid stroke identification and treatment, hospitals can significantly improve patient outcomes.